QUALITY AND EFFECTIVENESS IN ELECTRONIC TAX FILLING: A STUDY OF TAX-PAYER SATISFACTION - Siregar, Syahrizal; Supriyadi, Supriyadi; Hakim, Lukmanul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyse the quality and effectiveness of e-filling application by Indonesia tax payer. The theory adopted IS Success DeLone and McLean using three variables to measure the effectiveness of e-filling include user satisfaction, information quality, system quality, and service quality. Data collected through surveys conducted to taxpayers who have used Tax e-filling. PLS SEM and path analysis was applied to test the influences of the quality antecedents to user satisfaction with IS. The finding reveal that path coefficients provided a measure of the importance of each quality antecedent. The result show that Information quality, system quality, and service quality are increasing taxpayer satisfaction. This result also give evidence that the information quality, quality of system and service quality used by the organization positively affects the level of satisfaction of taxpayers. This study gives suggestion for Directorate General of Taxes could be sought by improving and increasing the information quality, system quality, use, and user satisfaction on e-filing system. This research gives empirical value that information quality, system quality and service quality have significant and positive effects on tax payers’ satisfaction. Keyword: Information Quality, System Quality, Service Quality, Tax Payer Satisfaction